Diastereoselective synthesis of novel heterocyclic scaffolds through tandem Petasis 3-component/intramolecular Diels–Alder and ROM–RCM reactions. Issue 68 (17th July 2017) - Ishoey, Mette; Petersen, Rico G.; Petersen, Michael Å.; Wu, Peng; Clausen, Mads H.; Nielsen, Thomas E.
Abstract : Complexity-generating tandem Petasis 3-component/intramolecular Diels–Alder and ROM–RCM reactions for the diastereoselective synthesis of sp 3 -rich heterocyclic compound libraries are presented. Abstract : A high-yielding, stereoselective and extraordinarily complexity-generating Petasis 3-component/intramolecular Diels–Alder reaction has been developed. In combination with ROM–RCM, rapid access to complex sp 3 -rich heterocyclic scaffolds amenable to subsequent functionalization and library synthesis is provided.